Laser Phototherapy (660 nm) Can Be Beneficial for Reducing Gingival Inflammation in Prosthodontics - Sávio José Cardoso Bezerra; Glauco Fioranelli Vieira; Carlos de Paula Eduardo; Patrícia Moreira de Freitas; Ana Cecilia Corrêa Aranha (Hindawi Limited, 2015)
Among the new technologies developed, low power lasers have enabled new approaches to provide conservative treatment. Low power lasers act at cellular level, resulting in reduced pain, modulating inflammation, and improved tissue healing. Clinical application of the low power laser requires specific knowledge concerning laser interaction with biological tissue so that the correct irradiation protocol can be established. The present case report describes the clinical steps involved in an indirect composite resin restoration performed in a 31-year-old patient, in whom low power laser was used for soft tissue biomodulation. Laser therapy was applied with a semiconductor laser 660 nm, spot size of 0.028 cm2, energy density of 35.7 J/cm2, mean power of 100 mW, and energy per point as 1 J, in contact mode, on a total of 2 points (mesial and distal), totaling 2 J of energy. The therapy with low power laser can contribute positively to the success of an indirect restorative treatment.